Cultivo de Digitalis mariana Boiss. ssp. heywoodii (P. Silva and M. Silva) Hinz sob omissão de nutrientes em sistema hidropônico e sob malhas coloridas: crescimento vegetativo e doseamento de cardenolídeos - Marafeli, Érica Alves Marques (2021)
Species of the Digitalis genus, commonly known as ‘Foxglove', are the main source of cardiotonic heterosides (CHs) of the cardenolide type, responsible for much of their pharmacological properties and therapeutic applications. The cardenolide glucoevatromonoside (GEV), produced in Digitalis mariana ssp. heywoodii has great medicinal value for effectively inhibiting the acyclovir-resistant Herpes simplex type 1 (HSV-1) virus, demonstrating anticancer activity in vitro. This paper aimed to evaluate the vegetative growth and accumulation of total cardenolides and glucoevatromonoside (GEV) in cultivated plants of Digitalis mariana ssp. heywoodii, in pots under different colored screens and a hydroponic system under omission of macro and micronutrients. For this purpose, a GEV dosage method by HPLC-DAD was first developed and validated, according to the criteria of the ICH guide - International Conference on Harmonization (ICH, 1996) and ANVISA Resolution RE nº 166 of July 24th, 2017 (BRASIL, 2017). Two agronomic experiments were installed. The first consisted of Digitalis mariana ssp. heywoodii seedlings cultivated under blue, red, and black photo converter screens and full sun. The second experiment consisted of seedlings cultivated in a hydroponic system, employing the missing element technique, with the individual omission of macro and micronutrients from the Hogland and Arnon (1950) solution. The complete Hogland and Arnon (1950) solution was used as the control. Growth parameters, morphology, protein accumulation, photosynthetic pigments, cardenolides, and GEV were analyzed. The differences between the groups evaluated were considered statistically significant according to the Tukey test (5%). The blue screen provided the highest amount of leaf dry matter (12.69 g), root growth (54.00 cm), leaf area (46.97 cm2), protein content (0.118 mg mL-1), and chlorophyll a (1.88 mg g-1). The blue and red screens showed no significant difference at the level of 5% significance (2.29% and 2.33%, respectively) for total cardenolides. The highest levels of GEV were found only in plants cultivated under the blue screen (26.0 μg/100g of plant material). The omission of nitrogen (N), phosphorus (P), sulfur (S), and manganese (Mn) did not affect the growth of the aerial part of the plants. Boron (B) and magnesium (Mg) deficiency caused a greater accumulation of total protein (0.066 and 0.062 mg mL-1, respectively). However, sulfur (S) deficiency caused a decrease of 51.9% compared to the full treatment. The nutrient limitation impacted the accumulation of total cardenolides in the following order: Cu = Fe = Mg = Ca > Mn = B = Zn > S = K = P = N = full. The chromatographic method developed and validated was successfully used in the quantitative analysis of GEV. Different light spectra and availability of macro and micronutrients affect vegetative growth, production of photosynthesizing pigments, proteins and total cardenolide, and GEV levels in Digitalis mariana ssp. heywoodii.